Internet Financial Reporting (IFR) disclosure position and firm value - Kamarul Baraini Keliwon; Zaleha Abdul Shukor; Mohamat Sabri Hassan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nowadays, Internet Financial Reporting (IFR) disclosure is the global way to display firm performance to investors and stakeholders. Hence, it is imperative that firms properly manage their IFR disclosure to ensure their existence is conspicuous to the world in order to foster their firm value. We believe that in order to manage IFR disclosure, firms would probably behave either ritualistically or opportunistically in terms of their IFR disclosure position. In this study, we propose a quantitative measurement for the IFR disclosure position, i.e. utilizing IFR presentation score, taking into consideration latest IFR rules and regulations worldwide as well as relevant extant empirical studies. Based on a sample of 320 Malaysian listed firms in year 2012, our regression analysis shows that our quantitative measurement for the IFR disclosure position variable has a positive association with firm value. We found that 87 firms, categorized as poor performing seems to manage their IFR disclosure position ritualistically. While 233 firms, categorized as well performing manage their IFR disclosure position opportunistically. Hence, our study provide circumstantial evidence that firms’ financial performance has a relationship with IFR disclosure position. In further analysis, our findings show that stakeholders seem to perceive ritualistic IFR disclosure’s position is empirically valid to value poor performing firms. However, stakeholders seem to negate the opportunistic IFR disclosure position in valuing well performing firms even though theoretically the opportunistic IFR disclosure position should be able to offer vast benefits that could enhance firms’ value. Our findings should be useful to firms and stakeholders likewise in making firms’ valuation taking into consideration the existence of firms’ financial performance and IFR disclosure position.